B Tools - Boulanger, Jean‐Louis (Formal Methods Applied to Complex Systems: Implementation of the B Method, 2014)
This chapter presents different types of tools used for the implementation of the B language. Both the commercial and freely‐distributed versions of Atelier B constitute high performance tools for learning the B language and for complex developments, but interfacing with other tools is difficult, although it is possible to use open source tools to prove proof obligations (POs) generated using Atelier B. The chapter also presents the ABTools environment, used to test extensions to the B language by generalizing existing grammars. It is divided into three sections: general principles; presentation of Atelier B and presentation of open source tools.